Pengembangan Buku Digital Interaktif Marbelis untuk Meningkatkan Keterampilan Menulis Kalimat SPOK bagi Peserta Didik Disabilitas Rungu - Febri Martha; Endang Pudjiastuti Sartinah; Wagino Wagino (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study addresses the challenges faced by students with hearing disabilities in writing sentences using the SPOK (Subject-Predicate-Object-Adverb) structure at SLBN Banjarsari Wetan, Madiun. Observations revealed that the primary obstacle is using conventional learning media not integrated with digital components. Therefore, this research aims to develop an interactive digital book called Marbelis to enhance SPOK sentence writing skills. Marbelis combines the features of interactive and digital books, offering structured materials on SPOK elements, visual flip-up pages, and word wall games accessible via QR codes. The research employs the ADDIE development model and follows an explanatory sequential design with a one-group pretest and post-test approach. The participants consisted of eight seventh-grade students with hearing disabilities. The product's feasibility was evaluated through expert validation, resulting in an average score of 90%, categorized as valid. Practicality assessment yielded an average score of 92%, indicating the media is highly practical. The effectiveness was tested using the Wilcoxon signed-rank test, with a significance value of 0.012 (p < 0.05), confirming a statistically significant improvement in students’ learning outcomes. The findings suggest that the Marbelis interactive digital book effectively improves SPOK sentence writing skills among students with hearing disabilities.